Diagnostic value of physical examination in children with mild head injury in comparison with computed tomographic (ct) scan findings - Farizal, Fadzil (2010)
Mild head injury in children results in a large number of radiological evaluation and hospital admissions each year around the world. Although some guidelines and proposals have been made in this area, there is still a great deal of controversy surrounding patients with briefloss of consciousness (LOC) and Glasgow Coma Scale (GCS) scores of 13-15. Recent studies have indicated that avoiding head CT scans in patients with LOC and a GCS scores 15 may be possible. The objective of this study was to determine the diagnostic value of physical examination for positive CT scan findings in children with mild head injury (GCS score 13-15) and with loss of consciousness or amnesia. From the result, the sensitivity, specificity and predictive values of a normal physical examination after mild head injury and loss of consciousness would also be calculated and analysed. A retrospective medical record review of patients aged 1 to 12 years old who were evaluated for mild head injury with LOC or amnesia at the emergency department of Hospital Besar Kuala Lumpur between January 2007 and June 2009. Subjects who met the inclusion criteria were selected for the study and the data recorded into the proforma. Data collected included age, gender, mechanism of injury, GCS on arrival, presenting symptoms, physical sign fmdings, head computed tomography (CT) results and further management of the subjects. The estimations of prevalence, sensitivity, specificity, positive predictive value, and negative predictive value were calculated, along with 95% confidence interval limits, using the Wilson score method. The agreement between physical examination and CT brain XII in children with mild head injury and with loss of consciousness or amnesia was calculated using Kappa test. 225 patients were included into the study (January 2007 to June 2009). Sixty-three percent (63%) of these patients were male, and thirty-seven (37%) were female Out of225 patients, 44(19.56%) patient had positive scan finding and 17 patients (7.56%) who had positive scan finding showed normal physical examination. Fifteen cases (6.7%) underwent neurosurgical intervention. For intracranial traumatic CT findings, sensitivity and specificity were 61.36% and 60.22% respectively. The agreement between physical examination and CT scan was found to be Kappa= 0.147 (p <0.05), 95% CI (0.035, 0.259). The present study showed that physical examination was significantly associated with positive CT scan finding (p=O.Ol ). However on further assessment of its predictive ability of a normal physical examination, and the findings of unacceptably low sensitivity and specificity, 61.36% and 60.22% respectively, a conclusion was made that intracranial pathology in children with minor head injury and having loss of consciousness or amnesia cannot be excluded on the basis of physical examination alone. The kappa value calculated only showed a slight agreement between these two variables.